Kembali ke Alam : Optimalisasi Pola Hidup Sehat Berbasis Literasi Lingkungan sebagai Upaya Menciptakan Lingkungan Ideal di SDN 01 Desa Sugihan - Jajim Fuadi; Daniza Alzura; Siti Baitul Mukarommah (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program was conducted at SDN 01 Desa Sugihan with the aim of increasing students' awareness and understanding of the importance of a healthy lifestyle integrated with environmental literacy. Elementary school students were chosen as the target group because they are in a critical stage of developing their mindset and daily habits. The program was carried out through three interactive and practical sessions. The first session introduced the importance of consuming healthy foods from nature through storytelling activities and planting kangkung (water spinach) as a healthy food source. The second session focused on personal hygiene by teaching and practicing proper tooth brushing and handwashing techniques. The third session encouraged students to engage in creative recycling activities by making lavender flowers from used straws and pencil holders from plastic bottles to instill environmental awareness and recycling values. The results showed an increase in students' knowledge and positive attitudes toward applying a healthy lifestyle and caring for the environment both at school and at home. Through engaging methods and hands-on activities, this program is expected to help students build sustainable healthy habits and become a generation that cares about health and environmental preservation.